The 3 C's of anthropomorphism: Connection, comprehension, and competition. Issue 1 (19th September 2019) - Yang, Linyun W.; Aggarwal, Pankaj; McGill, Ann L.
Abstract: Anthropomorphism, or imbuing nonhuman entities with human traits, is widely prevalent in the marketplace. The last decade of consumer research demonstrates that when imbued with human characteristics, anthropomorphized brands and products become active participants in the consumption experience and are viewed and treated fundamentally differently than those viewed simply as objects. We identify three dimensions around how consumers relate to anthropomorphized entities: connection, comprehension, and competition. The first two C's highlight how anthropomorphized brands and products benefit consumers by fulfilling belongingness needs (connection) and helping consumers understand unfamiliar situations and products (comprehension). In contrast, the competition dimension highlights how anthropomorphized brands and products are perceived as adversaries or potential threats to consumers' individual goals. By identifying competition as the third C, we illuminate self‐protection as an additional motivation that shapes consumers' responses to anthropomorphized entities—a motivation that has not been directly accounted for in previous theorizing.